Relationship between Diet and Physical Activity with Blood Pressure of Hypertension Patients in the Gandus Palembang Health Center 2021 - Eva Susanti; Ira Kusumawaty; Emmy Asfara (CV. AFDIFAL MAJU BERKAH, 2022)
Hypertension can be a serious problem because when it is not well taken care of as early as possible, it will develop and cause dangerous complications such as heart failure, congestive kidney failure, stroke, sight problem and kidney problem. Hypertension can be prevented by avoiding the factors that cause it. This study aims to find out and analyze the relationship of diet and physical activity with blood pressure of people with hypertension. Type of analytic observational research with cross sectional design. Sampling in this study using non probability sampling technique, with a purposive sampling approach of 42 respondents. The results of data analysis conducted are univariate analysis and bivariate analysis with Chi Square test. From the data analysis carried out, namely univariate analysis and bivariate analysis with Chi Square test. The results of this study showed that 64.0% had a poor diet with uncontrolled hypertension, and 69.6% had mild activity with uncontrolled hypertension. This study showed that there was a significant relationship between diet and blood pressure in hypertension patients (p-value 0.004, OR=8.296) significantly and physical activity significantly increased blood pressure in hypertensive patients (p-value 0.002). So that further researchers are advised to consider other factors that can affect the increase in blood pressure in patients with hypertension, so that they have different criteria and maximize research results.